Zali Enterprise / Muhammad Syafiq Supian - Supian, Muhammad Syafiq (2021)
Wan Mohammad Radzli or well known as Zali Enterprise is chosen to be my assignment. There are many reasons that makes me choose him. He has been my idol since I was young. When I was young, I always wanted to be successful young entrepreneur like him. His characters and skills in handling their business has been proven by winning an award in carnival organized by Kelantan Trade. He has been in this food industry food 25 years. He has been through ups and downs through his business since he used his own capital without any funding from investors.